Lade Daten...
randRange(2,5) randRange(2,5) A*B

Bringe den folgenden Ausdruck in die Form log(c).

\Large\log(A) + \log(B)

C

Benutze folgendes Logarithmusgesetz: \log(a) + \log(b) = \log(a \cdot b).

\log(A) + \log(B) = \log(A \cdot B)

= \log(C)

Bringe den folgenden Ausdruck in die Form log(c).

\Large\log(C) - \log(A)

B

Benutze folgendes Logarithmusgesetz: \log(a) - \log(b) = \log(\frac{a}{b}).

\log(C) - \log(A) = \log(\frac{C}{A})

= \log( B )

Bringe den folgenden Ausdruck in die Form log(c).

\Large A\log(B)

pow( B, A )

Benutze folgendes Logarithmusgesetz: n \cdot \log(a) = \log(a^{n}).

A\log(B) = \log(B^{A})

= \log(pow( B, A ))